Comparative androgenetic competence of various species and genotypes within the genus Pisum L. - Bermejo, Carolina Julieta (2020)
In pea breeding is important to shorten the generation cycles to obtain homozygosity quickly. Doubled haploid technology is important to attain this purpose and androgenesis is the most promising tool for induction of haploids in legumes. Commercial pea varieties have been described as recalcitrant to this approach but very little is known regarding the androgenic competence of pea relatives. In this work, a comparative study of the androgenic response among different taxa of the genus Pisum was undertaken. We cultured anthers of 11 pea materials from the primary and secondary genepools under the same experimental conditions, and studied their competence to produce calli and plants in vitro. Significant differences were found in the percentage of callus and plant production between the different species and subspecies. The two wild forms Pisum fulvum Sibth. & Sm. and Pisum sativum subsp. elatius (Bieb.) Aschers. & Graebn. regenerated shoots from anther culture with the highest efficiency (67% and 38%, respectively), becoming potential sources of androgenic competence. Among the cultivated genotypes of P. sativum, the botanical variety arvense regenerated shoots with the highest percentage (40%) also being a good candidate to study androgenesis. The commercial varieties tested showed significant differences in the callus and plant production, with Primogénita (FCA-INTA) and B101 giving the best results although with low plant regeneration percentages (17% and 11%, respectively). P. fulvum, P. sativum subsp. elatius and P. sativum subsp sativum var arvense were identified as highly responsive to anther culture, useful to transfer androgenesis competence to recalcitrant commercial varieties.